What is the accuracy of autofluorescence imaging in identifying non‐polypoid colorectal neoplastic lesions when reviewed by trainees? A pilot study. Issue 4 (5th December 2012) - Odagaki, Tomoyuki; Sakamoto, Taku; Sekiguchi, Masau; Sato, Chiko; Tamai, Naoto; Otake, Yosuke; Nakajima, Takeshi; Matsuda, Takahisa; Saito, Yutaka
<x xml:space="preserve">Abstract</x> Background and Aim Non‐polypoid colorectal neoplasms are difficult to identify using conventional white light (WL) colonoscopy. The aim of the present pilot study was to compare an autofluorescence imaging (AFI) system with conventional WL colonoscopy for the identification of non‐polypoid neoplasms by trainees in a colonoscopic observational situation. Methods We selected clear images with both AFI and WL in the same field taken by experts at the National Cancer Center Hospital, Tokyo, from December 2009 to November 2010. One hundred and eighty sets of images (137 non‐polypoid neoplasms and 43 without neoplasm) were selected. The images were reviewed by two trainees without AFI experience. After attending a short educational lecture on the AFI system, the reviewers determined the presence of lesions in the randomly arranged images. The accuracy of AFI and WL for identifying non‐polypoid neoplasms by trainees was assessed. Results The sensitivity and specificity for identifying non‐polypoid neoplasms by trainees was not significantly different between AFI and WL. However, the specificity tended to be lower in AFI images than in WL images. Conclusions False‐positive results tended to be more frequent for the AFI images than for the WL images. Further improvements in the technology and resolution are necessary for the AFI system to be useful for the detection of colorectal neoplasms. At present, clinical application of the AFI system may require more extensive structured training to improve its accuracy in the identification of non‐polypoid colorectal neoplasms.